ANALISIS PERANAN BADAN USAHA MILIK DESA ( BUMDES ) DALAM MENUNJANG PEREKONOMIAN MASYARAKAT DESA MELALUI PENGELOLAAN SAMPAH (Studi BUMdes Prai Meke Kecamatan Praya Tengah Kabupaten Lombok Tengah ) - Dewi Marlina; Sahar, Sahar; Laili Hurriati; Muhammad Sayuti; Sasmita, Vika; Putra Ramadhan, Radhitya (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
This research is entitled "ANALYSIS OF THE ROLE OF VILLAGE-OWNED BUSINESSES IN SUPPORTING THE ECONOMY OF VILLAGE COMMUNITIES THROUGH WASTE MANAGEMENT" The problem raised in this study is How the Role of Village-Owned Enterprises (BUMdes) in an effort to support the economy of village communities through Waste Management. This research explores the role of Village-Owned Enterprises (BUMDes) in improving the community's economy through waste management in Prai Meke Village, Central Lombok. The program aims to manage local resources and improve social welfare. With the increasing amount of waste, waste management becomes essential to achieve sustainable development, related to health issues, climate change, and poverty reduction. This research uses descriptive qualitative method, the results show that BUMDes contributes positively by creating jobs and supporting the 'Waste Free Village' program initiated to utilize recyclable waste. This research successfully creates jobs, increases community creativity, reduces dependency, and improves environmental health. Thus, BUMDes serves as a local economic driver and facilitator of community empowerment, strengthening self-reliance and social welfare in the village.